Democracy : A Very Short Introduction - Crick, Bernard (Karachi Oxford University Press, 2002)
This is a short history of the doctrine and practice of democracy, and of the usages and practices associated with it in the modern world. It argues that democracy is a necessary but not a sufficient condition for good government, and that ideas of the rule of law, and of human rights, should in some situations limit democratic claims.
Include Illustrations and Index.
Keywords: Democracy -- History -- Japan